Informational Aspects of the Theory of Political Security - V. V. Borshchenko; Yu. V. Kosov (Управленческое консультирование, 2018)
The article examines the existing theoretical approaches to the explication of the political security allocated to such part of it as information and political security and the author’s interpretation of the latter. The boundaries of the political-information security, allowing to separate it from other species-specific security information. The influence of information on the formation of informationpolitical threats that affect information and political security of the country.